Smart Shopping With Enhanced User Experience - et. al., Shanmugam. M, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Artificial Intelligence is considered as both engineering and scientific method of producing machines with intelligence. AI is all about striving to create machines or software to imitate and eventually take over from human actions and intellect. Automation can or cannot be dependent on Artificial Intelligence. The grooming of automation has been changed to a middle progress in between the evolution of first and third revolution production in industry with automatic trying and organizes mechanisms, systematic effort, operating apparatus and the well-known computer systems. All of the nomenclatures of automation that have manifested surrounding us are conjugated by skillful programming and a set of laws. The current automation in the shopping experience has been a vast technology improvement used by people. But many of the basic requirements are not met. The existing system scans the product only for the price while some systems do not update user preferences. The age ranged recommendations are not taken into account. This process does not upgrade itself and is the same even if the preferences of people change. They only perform automating billing at the counter. Our system scans the face and detects the person’s gender and age to show recommendations accordingly. The searching process for the needed product is made simpler by showing the location on the blueprint of the shop. Each person is assigned an ID and their previous purchases are stored. This information is used to train the system. The application is evaluated the following feature such as context aware, progressive, intelligent, non-human interaction and security. The app is useful for shop owners to improve the business. It also helps the customers to have an automated and happier shopping experience.